Correction to: A solution algorithm for integrated production-inventory-routing of perishable goods with transshipment and uncertain demand - Liu, Peide; Hendalianpour, Ayad; Razmi, Jafar; Sangari, Mohamad Sadegh (Complex & intelligent systems, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s40747-021-00311-2